PRODUCTION D’ATTIEKE (COUSCOUS A BASE DE MANIOC FERMENTE) DANS LA VILLE D’ABIDJAN - Regina, Krabi Ekoua; Antoine, Assamoi Allah; Fafadzi, Ehon Ayawovi; Diawara, Bréhima; Sébastien, Niamké Lamine; Philippe, Thonart (European Scientific Journal, ESJ, 2015)
A socio-economic and technological survey was conducted encompassing producers of attieké (a fermented cassava couscous) in Abidjan in order to determinate difficulties for the promotion of this activity. It was found that small women’s individual businesses, with low education level, decide on their activity according to their capacity and the socioeconomic environment. They are integrated in the family economy by both the production place, which is confused with the producer residence, that by the time sharing between productive activities and the family activities. The production is carried out traditionally in arduous conditions according to the traditional experience of the producer and not on a theoretical and rational knowledge. Three types of attiéké (garba, agbodjama, normal) occurred whose the most met nationally is the normal type, which is an acid food, relatively poor in protein, high moisture content over than 45% and with an absence of Salmonella, which can ensure consumer safety. Professionalization and training of producers, establishment of good practice guides, labeling and standardization, are among other proposals to promote this activity.